The Effectiveness of Group Counseling with Motivational Interviewing Approach to Improve Academic Hardiness - Larasati Ayuningtias, Arnika Dewi; Eddy Wibowo, Mungin; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2023)
Academic hardiness as an ability to gain good achievement in learning, have commitment, and control over what they obtain is truly needed by students to face academic challenges. This study strived for examining the effectiveness of group counseling with a motivational interviewing approach to improve the academic hardiness of Senior High School (SMA) students. It used a motivational technique treatment for five sessions and analyzed students’ pretest and posttest data using a Wilcoxon test. In terms of subject, this study invited eight students of SMAN 9 Semarang, consisting of four males and four females sampled from 290 students. Findings revealed that this technique was effective to improve the academic hardiness of SMA students. Thus, counselors are recommended to implement the group counseling with a motivational interviewing approach to improve the academic hardiness of SMA students.